Determining Cycle Times for Packing in Distribution Centres - Weiblen, Judith (Wissenschaftliche Berichte des Instituts für Fördertechnik und Logistiksysteme des Karlsruher Instituts für Technologie, 2014)
Scope of this work is to determine cycle time formulas for packing in distribution centres. No such formulas exist today, even if it is the second most important process after picking. Based on examining packing, morphological boxes showing time influencing parameters are derived. The most significant parameters are identified using analysis of variance (ANOVA). Cycle times are determined and applied to cases. These prove that the formulas can be used to calculate the time required for packing.